Leukoaraiosis Mediates the Association of Total White Blood Cell Count With Post-Stroke Cognitive Impairment - Shan, Wanying; Xu, Liang; Xu, Yuan; Qiu, Zhuoyin; Feng, Jie; Zhao, Jie; Wang, Jingwen (Frontiers in Neurology, 2022)
Background and purpose: Inflammatory response may play a vital role in contributing to cognitive function. However, the total white blood cell (WBC) count has been little investigated in relation to post-stroke cognitive impairment (PSCI), and the role of leukoaraiosis in this relationship is not well established. We aimed to examine the total WBC count in relation to PSCI and whether the association was mediated by leukoaraiosis. Methods: We prospectively analyzed consecutive patients with first-ever ischemic stroke during October 2020 to June 2021. Total WBC count was measured after admission. Cognitive function evaluations were performed at the 3-month follow-up using Mini-mental State Examination (MMSE). PSCI was defined as a MMSE score < 27. Results: A total of 276 patients (mean age, 66.5 years; 54.7% male) were included in this analysis. Among them, 137 (49.6%) patients experienced PSCI. After adjustment for potential confounders, increased total WBC count was associated with a higher risk of leukoaraiosis (per 1-SD increase, odds ratio [OR], 1.48; 95% confidence interval [CI] 1.14–1.92; P = 0.003) and PSCI (per 1-SD increase, OR, 1.49; 95% CI 1.12–1.97; P = 0.006). Furthermore, mediation analysis demonstrated that the association between total WBC count and PSCI was partly mediated by leukoaraiosis (the regression coefficient was changed by 9.7% for PSCI, and 12.4% for PSCI severity, respectively) Conclusions: Increased total WBC count is a risk factor for PSCI. The presence of leukoaraiosis was partially responsible for the PSCI in patients who had a higher total WBC count.